Desain Pembangkit Listrik Tenaga Surya Tipe Rooftop On Grid – System Pada Gedung Laboratorium Teknik Elektro Universitas Riau - Yakin, Khusnul; Rajagukguk, Antonius (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Fossil resources will be depleted and not a sustainable option for the future. Fossil energy needs to be reduced in use and replaced by renewable energy sources. Solar energy is an alternative energy source with photovoltaic (PV) because of its unlimited availability. The PV system can be placed on top of a building and the maximum utilization of solar energy and utilizes the roof area to reduce investment costs in PV construction. This study designs and simulates a Rooftop PV On-Grid System in the Electrical Engineering Laboratory Building, Riau University. Design layout using Sketchup Pro 2017 software and PV mini-grid simulation using Marlab R2016a software. The results of this study resulted in 144 modules with a module power of 250 Wp from the total size of the roof of the building used and the total power was 36 kWp. The output of the PV module will be continued with the Buck Converter series to reduce the output as desired. Based on the results of the power test with 1000 W / m2 irradiation, the power obtained is 35,850 Wp. The resulting converter circuit efficiency is 98%. The system is designed to be connected and synchronous to the electricity network, when the load is greater than the PLTS power, the system regardless of the load is replaced by the PLN Electricity Network. Keywords: PLTS Rooftop, Grid-Connected, Buck Converter, Sketchup Pro 2017, Matlab R2016a